Epidemiology of hidradenitis suppurativa in Germany – an observational cohort study based on a multisource approach. (8th October 2019) - Kirsten, N.; Petersen, J.; Hagenström, K.; Augustin, M.
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic, debilitating inflammatory skin disease. In Germany, there are no population‐based data on the epidemiology of HS. Objectives: The objective of this study was to examine the occurrence of HS in inpatient as well as in outpatient settings. Methods: We used three data sources for analysing the prevalence, incidence and case‐related occurrence of HS in different settings: data of two German statutory health insurance (SHI) companies and hospital discharge data provided by the Federal Statistical Office. The studied period was from 2010 to 2015. Results: In a representative sample of about 2.3 million insurees (out of 5.9 million total persons) of the SHI DAK‐Gesundheit, 791 were diagnosed with HS in 2010. This coding prevalence of 0.03% is in accordance with the data of another SHI (Barmer) on about 9 million total insurees. In 2015, at least 34.7% of incident persons with HS had one potential misdiagnosis in 2014. Conclusion: This population‐based study analyses the prevalence and incidence of HS in Germany. The coding prevalence of 0.03% observed in two independent SHI data sets is lower than expected. The findings of considerable potential misdiagnosis add to the underdiagnosis of HS in general and underline the need for future strategies to early detection and valid diagnosis of HS.